2016
DOI: 10.7150/jca.15620
|View full text |Cite
|
Sign up to set email alerts
|

MiR-193a-5p Targets the Coding Region of AP-2α mRNA and Induces Cisplatin Resistance in Bladder Cancers

Abstract: Transcription factor AP-2 alpha (AP-2α or TFAP2A) is a newly identified prognostic marker of chemotherapy; its expression is positively correlated with chemosensitivity and survival of cancer patients. Using computational programs, we predicted that the coding region of AP-2α gene contains a potential miRNA response element (MRE) of miR-193a-5p, and the single nucleotide polymorphism (SNP) site (c.497A>G, rs111681798) resides within the predicted MRE. The results of luciferase assays and Western blot analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 26 publications
0
42
0
Order By: Relevance
“…Several miRNAs, including miR-34a [ 9 ], miR-375 [ 8 ], miR-124 [ 10 ], miR-205 [ 11 ] and miR-21 [ 12 ] have been implicated in tumor drug resistance. Recent studies showed that miR-193a-5p but only suppresses tumor growth, but also promotes tumor progression through regulating cell proliferation [ 13 , 14 ] and apoptosis, as well as through inducing drug resistance [ 15 , 16 ]. A previous study reported that miR-193a-3p, another mature miRNA of miR-193a precursor family, regulates the multi-drug resistance of bladder cancer by targeting the LOXL4 gene [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several miRNAs, including miR-34a [ 9 ], miR-375 [ 8 ], miR-124 [ 10 ], miR-205 [ 11 ] and miR-21 [ 12 ] have been implicated in tumor drug resistance. Recent studies showed that miR-193a-5p but only suppresses tumor growth, but also promotes tumor progression through regulating cell proliferation [ 13 , 14 ] and apoptosis, as well as through inducing drug resistance [ 15 , 16 ]. A previous study reported that miR-193a-3p, another mature miRNA of miR-193a precursor family, regulates the multi-drug resistance of bladder cancer by targeting the LOXL4 gene [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, miR-193a-5p has been found to be involved in multiple cancers, such as esophageal squamous cell carcinoma ( 14 ), bladder cancer ( 15 ), primary bone tumors ( 16 ), osteosarcoma ( 17 ), colorectal cancer ( 18 ) and endometrioid endometrial adenocarcinoma ( 19 ). Some noted pathways such as the PI3K/AKT signaling pathway, PTEN/AKT signaling pathway and mTOR signaling pathway have been implicated in the oncogenesis of different tumors and as therapeutic drug targets ( 20 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results of rescue experiments showed that the effect of decreased CRC cell proliferation and invasion caused by circRNA_0000392 knockdown was offset by inhibition of miR-193a-5p. It has been reported that miR-193a-5p mainly contribute as a tumor suppressor in a variety of cancers [33][34][35], and the interaction of circRNA_0000392 with miR-193a-5p attenuated the tumor suppressor e ciency of miR-193a-5p. Our results demonstrated that circRNA_0000392 serves as an oncogene by sponging the miR-193a-5p in CRC.…”
Section: Discussionmentioning
confidence: 99%